Coupling aerodynamics to vehicle dynamics in transient crosswinds including a driver model. (15th October 2016) - Winkler, Niklas; Drugge, Lars; Trigell, Annika Stensson; Efraimsson, Gunilla
Highlights: Coupling aerodynamics with vehicle dynamics to predict crosswind performance. Driver in the loop for a realistic scenario. On-road simulations to capture the correct head wind angle for a yaw motion. Dynamic coupling with feedback necessary when large yaw angles are expected. Abstract: In this paper we assess the order of model complexity needed to capture a vehicle behaviour during a transient crosswind event, regarding the interaction of the aerodynamic loads and the vehicle dynamic response. The necessity to perform a full dynamic coupling, including feedback in real-time, instead of a static coupling to capture the vehicle performance both with respect to aerodynamics and the vehicle dynamics is evaluated. The computations are performed for a simplified bus model that is exposed to a transient crosswind. The aerodynamic loads are obtained using Detached Eddy Simulation (DES) with the overset mesh technique coupled to a single-track model for the vehicle dynamics including a driver model with three sets of controller parameters to obtain a realistic scenario. Two degrees of freedom are handled by the vehicle dynamics model; lateral translation and yaw motion. The results show that the full dynamic coupling is needed for large yaw angles of the vehicle, where the static coupling over-predicts the aerodynamic loads and in turn the vehicle motion.